Partisipasi Guru Dalam Pengambilan Keputusan Untuk Pengembangan Organisasi - Mutya Ayu Henirwan; Naifa Filda Putri; Ermita; Fifin Wildanah (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Teacher participation in decision-making is a crucial element in the effective development of school organizations. This article aims to analyze the role of teachers in school decision-making processes and their impact on educational management effectiveness. The research employs a qualitative approach using a literature study technique from various relevant sources. The findings indicate that teacher involvement in school policy formulation contributes to increased work motivation, collaboration among educators, and innovation in teaching methods. Additionally, a participatory approach fosters a more conducive and harmonious work environment. However, several challenges remain in its implementation, such as centralized leadership systems, time constraints, and a lack of participatory leadership training. To overcome these obstacles, strategies such as fostering an inclusive school culture, collaborative leadership training, and utilizing technology in decision-making processes are required. With the proper implementation of these strategies, teacher participation can be optimized to enhance school organizational effectiveness and overall education quality.